Organizational stress and job satisfaction in military personnel - Rus, Mihaela; Sandu, Mihaela Luminita; Macsim, Lucia Giorgiana; Milea, Valentina (Technium Social Sciences Journal, 2022)
As we well know, the military field is a complex field, marked by intense experiences and borderline situations, and, in this context, psychology plays a significant role in knowing the explanation, but also predicting psychic reactions and human behavior in these situations; optimizing human capacities and resources in order to achieve the desired results; and above all, preventing, reducing/treating the mental consequences that may arise from participating in demanding events, both physically and mentally (Popa, 2019). These were the premises from which we started in addressing this theme, wanting to turn our attention to two key elements of the military environment. It’s about occupational stress and job satisfaction and, perhaps most importantly, the relationship they are in.